Polydimethylsiloxane/divinylbenzene overcoated fiber and its application to extract and analyse wine volatile compounds by solid-phase microextraction and gas chromatography coupled to mass spectrometry: direct immersion, headspace or both?. (October 2021) - Lenti, Lucia; Scortichini, Serena; Pacetti, Deborah; Cespi, Marco; Fiorini, Dennis
Graphical abstract: Highlights: A model with generic wine chemical composition, including volatiles, was prepared. Commercial overcoated fiber was used to extract volatiles from wine and wine model. Headspace, direct immersion and combined direct immersion-headspace were compared. Different extraction temperatures (T) were compared (25, 35 and 45 °C). Extraction mode, contrarily to T, provided an important effect on extraction efficiency. Considering analytes volatility, combined mode provided a more balanced extraction. Abstract: In this study, a comparison of the efficiency of the commercially available polydimethylsiloxane/divinylbenzene (PDMS/DVB) overcoated (OC) fiber used in direct immersion (DI) or in headspace (HS), has been performed by extracting volatiles through solid-phase microextraction (SPME) from a red wine and from a wine model to confirm the results. It was also investigated if a combination of DI followed by HS in a single assay (DI-HS) can provide improvements as compared to the use in DI or in HS only. Furthermore, the use of OC fiber in HS mode was compared with the use of the triphasic phase (TP, in PDMS/CAR/DVB), known to provide good results in this application. To have information also on fiber specificity, the detected analytes were subdivided into three classes depending on their boiling point. Results show that: OC fiber gives slightly better performance as compared to TP fiber, demonstrating a high efficiency of the OC fiber also in HS mode. Then, comparing the use of the commercial OC fiber in HS, DI and in the combined DI-HS mode, explored for the first time in this study to extract volatiles from wine, the combination DI-HS resulted to provide a more balanced efficiency for all the three groups of analytes, thus being a good compromise when the analytes have a broad range of volatility. Principal component analysis (PCA) and the design of experiment (DoE) were exploited to plan experiments and to help interpreting the results, highlighting that the combined DI-HS approach can be successfully applied to the characterization of wines and of other matrices, where analytes of interest have a wide range of volatility.